Disaster Management Problems in Indonesia: Urgency Of "Migrant Worker" Data Collection, Learning From Conditions During The Covid-19 Pandemic - Alfana, Muhammad Arif Fahrudin; Pitoyo, Agus Joko; Rohmah, Hidayati Nur; Laudiansyah, Rizki (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
The COVID-19 pandemic has opened a new view that management of our population administration has not been good. The weakness is the unavailability of migrant worker database which is very important when a disaster like this occurs. This paper explains the urgency of migration data, learning from the Covid-19 pandemic. This research is a quantitative and qualitative research. The method in this paper uses literature study and interviews with informants. Data analysis uses descriptive analysis. In conclusion, migration data play an important role when outbreaks such as COVID-19 occur. Migration data will be used as a basis for tracking population is doing internal migration. With this data, the government in the area of origin and destination can carry out various kinds of protection for the population. innovations carried out by the Population and Civil Registration Agency or other agencies in each district and city are needed to integrate this data into their systems. This internal migration data will later be used by the government as a good decision support system whenever needed.